일부 대학생의 상악 대구치 임상치관의 형태와 크기 - 전은숙(Eun-Suk Jeon); 이정화(Jung-Hwa Lee) (한국콘텐츠학회 논문지, 10(7), 2010)
This study was implemented among 100 students of C College of Public Health who have healthy permanent dentition in order to measure the morphology and sizes of clinical crowns of permanent maxillary molars. The following are conclusions of this study. 1. The cusp height, crown width, crown thickness of clinical crowns appeared to be bilaterally symmetrical. 2. The strong development of the buccal groove showed to be superior in the right first molar. The appearance rate of the buccal pit was high in the right first molar also. 3. The type 4th cusp appeared as 100% in the left and right first molars, and 78%, 75% in the left and right second molars respectively. 4. The distal lingual cusp(DLC) size were bilaterally symmetrical in the type 4th cusp. 5. As for the distance between two cusp tips, it was large between mesial cusp tips in all of the first and second molars at both sides. 6. Development of the Carabelli's cusp was high in both the left and right first molars. 7. The appearance rate of the oblique ridge was 87.0% in the right first molar, 73.0% in the right second molar, 88.0% in the left first molar, and 73.0% in the left second molar. This is considered to be caused by people who have mild dental crown caries in their first molars. 8. The appearance rate of the mesial marginal ridge tubercle(DMRT) was high in both of the left and right first molars. That of the distal tubercle was 16.0% in the right first molar, 26.0% in the right second molar, 14.0% in the left first molar, and 21% in the left second molar. 이 연구는 상악 대구치 임상치관의 형태 및 크기를 계측하기 위해 건강한 영구치열을 갖는 C보건대학생 100명을 대상으로 다음과 같은 결론을 얻었다. 1. 임상치관의 교두높이, 치관폭, 치관두께는 좌우 대칭관계를 보였다. 2. 협면구의 강한 발육은 우측 제1대구치에서 우세함을 보였고, 협면소와는 우측 제1대구치에서 높은 출현률을 보였다. 3. 4교두형은 좌 우측 제1대구치에서 100%, 좌 우측 제2대구치에서 각각 78%, 75%로 나타났다. 4. 4교두형일때 원심설측교두 크기는 좌, 우 대칭관계를 보였다. 5. 교두정간 거리는 좌 우측 제1,2대구치 모두 근심 교두정간 거리가 컸다. 6. 카라벨리 교두의 발달은, 좌 우측 모두 제1대구치에서 높은 발육을 보였다. 7. 사주융선의 출현률은 우측 제1대구치에서 87.0%, 우측 제 2대구치에서는 73.0%의 출현율을 보였고, 좌측 제1대구치에서는 88.0%, 좌측 제2대구치에서는 73.0%로 이는 제1대구치에서 약한 치관우식증을 가지고 있는 사람 때문인것으로 사료되었다. 8. 근심변연융선결절 출현율은 좌 우측 모두 제1대구치에서 높은 출현율을 보였다. 원심부 결절은 우측 제1대구치에서 16.0%, 우측 제 2대구치에서 26.0%였고, 좌측 제1대구치에서 14.0%, 좌측 제2대구치에서 21.0%의 출현율을 보였다.